Installing & configuring Microsoft Windows server 2012 (exam 70-410) - Long, Mark.; Safari eBooks ([S.l.] : Virtual Training Company, 2013)
"Microsoft's Server operating systems have powered business for over 20 years. In the beginning, it was all about connectivity in the local area network; now it's all about connectivity in the cloud. Microsoft calls Server 2012 "the Cloud OS" and is branding it as being 'built from the cloud up.' Their goal with this product is to deliver the power of many servers with the simplicity of one. Achieving a Microsoft Certification on this product is an excellent career move. In this VTC course, Mark Long brings 20+ years of experience with Microsoft technologies along to help you understand the features and functionalities of Windows Server 2012 from the standpoint of preparing for certification exam 70-410 Installing and Configuring Microsoft Windows Server 2012."--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed Feb. 25, 2014).
Presenter, Mark Long.
Keywords: Electronic data processing personnel -- Certification; Microsoft Windows server -- Examinations -- Study guides; Computer networks -- Examinations -- Study guides; Electronic books